2000
DOI: 10.1083/jcb.151.6.1221
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Cd34 and Myf5 Defines the Majority of Quiescent Adult Skeletal Muscle Satellite Cells

Abstract: Abstract. Skeletal muscle is one of a several adult postmitotic tissues that retain the capacity to regenerate. This relies on a population of quiescent precursors, termed satellite cells. Here we describe two novel markers of quiescent satellite cells: CD34, an established marker of hematopoietic stem cells, and Myf5, the earliest marker of myogenic commitment. CD34 ϩ ve myoblasts can be detected in proliferating C2C12 cultures. In differentiating cultures, CD34 ϩ ve cells do not fuse into myotubes, nor expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

38
723
2
14

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 805 publications
(794 citation statements)
references
References 74 publications
38
723
2
14
Order By: Relevance
“…Four MRFs (myf5, mrf4, MyoD, myogenin) constitute this family. Except for myf5 (Beauchamp et al, 2000) undifferentiated satellite cells do not express these factors. Activation of satellite cells for muscle regeneration is marked by expression of MRFs in a precisely coordinated temporal pattern (Yun and Wold, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Four MRFs (myf5, mrf4, MyoD, myogenin) constitute this family. Except for myf5 (Beauchamp et al, 2000) undifferentiated satellite cells do not express these factors. Activation of satellite cells for muscle regeneration is marked by expression of MRFs in a precisely coordinated temporal pattern (Yun and Wold, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…More intriguingly, SCs are highly heterogeneous 18,19 , and recent studies have shown that different levels of Pax7 expression produce two subpopulations of SCs-Pax7 Hi and Pax7 Lo -that have distinct biological features in mice 20 . Pax7 Lo cells are primed more for myogenic differentiation and less for self-renewal and higher metabolic status than Pax7 Hi cells.…”
mentioning
confidence: 99%
“…Myf5 is a transcription factor that contains a basic helix-loop-helix DNA binding domain and belongs to the muscle regulatory factors family. In adult mice, it is considered a typical satellite marker, expressed by quiescent satellite cells and is upregulated during muscle regeneration [26,27]. This makes it an excellent marker of myogenic specification.…”
Section: Bm Cells Enriched For Hsc Surface Markers Undergo Myogenic Smentioning
confidence: 99%